2014
DOI: 10.1073/pnas.1400513111
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 drives psoriatic inflammation via distinct, target cell-specific mechanisms

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by abnormal keratinocyte proliferation and differentiation and by an influx of inflammatory cells. The mechanisms underlying psoriasis in humans and in mouse models are poorly understood, although evidence strongly points to crucial contributions of IL-17 cytokines, which signal via the obligatory adaptor CIKS/Act1. Here we identify critical roles of CIKS/Act1-mediated signaling in imiquimod-induced psoriatic inflammation, a mouse model that shares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 45 publications
5
128
0
Order By: Relevance
“…The mechanism by which imiquimod induces psoriasis-like skin inflammation is not fully understood, although IL-17 cytokines like IL-17A, IL-17C, and IL-17F are believed to play important roles (23,43). The adaptor protein Act1 is one of the key components in the IL-17 signaling pathway (44), and recently Act1-mediated signaling was demonstrated to play an essential role in imiquimodinduced psoriasis-like skin inflammation (45). Although IL-17 has been demonstrated to regulate IκBζ through an Act1-dependent mechanism in mice (46,47) and humans (19), the exact signaling mechanism involved needs still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which imiquimod induces psoriasis-like skin inflammation is not fully understood, although IL-17 cytokines like IL-17A, IL-17C, and IL-17F are believed to play important roles (23,43). The adaptor protein Act1 is one of the key components in the IL-17 signaling pathway (44), and recently Act1-mediated signaling was demonstrated to play an essential role in imiquimodinduced psoriasis-like skin inflammation (45). Although IL-17 has been demonstrated to regulate IκBζ through an Act1-dependent mechanism in mice (46,47) and humans (19), the exact signaling mechanism involved needs still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Il23p19-, Il17ra-, and Act1-deficient mice are protected from IMQ-induced psoriasis compared with wildtype mice. [103][104][105] K5.Stat3C transgenic mice in which Stat3 is constitutively activated in keratinocytes develop skin lesions similar to those of human psoriasis. 106 Either neutralization of IL-17 or deletion of the Il17a gene ameliorates 12-O-tetradecanoylphorbol-13-acetate-induced psoriasis in these mice.…”
Section: Il-17dmentioning
confidence: 99%
“…It is characterized by abnormal keratinocyte proliferation and differentiation, and by an influx of inflammatory cells [71]. Inhibition of the excessive keratinocyte proliferation represents a main target in the treatment of psoriasis [72].…”
Section: Psoriasismentioning
confidence: 99%